The Future Role of Physical Touchpoints in Luxury Retailing - Sophie Schüller; Daniel Dietrich; Lorenz Spielmann (Marketing Review St.Gallen, 2018)
Conforming with the changing dynamics of physical retailing in general, luxury retailing has not been spared from extensive market transitions and uncertainty around the future relevance of physical touchpoints. Based on an exploratory investigation of the future role of physical touchpoints, this study highlights the relevance of physical distribution not merely being a tactical activity but an essential strategic premise for luxury retailing in various terms.
Keywords: 650